¿Unas elecciones de verdad? Autenticidad, representación y conflicto en los concursos de Reinas Indígenas de Guatemala - Gemma Celigueta (Journal de la Société des Américanistes)
In this article I will delve into de history of the Indigenous Queens Pageants in Guatemala. The analysis reflects on different ways of representing what is Indigenous and what is Maya in this country. My focus will be on the conflicts and debates these contests arouse in relation to their authenticity. I want to question the relationship between an « aesthetic » representation and a « political » representation of the Indigenous People.